In Vivo Interactions of Autoantibodies to Factor VIII with the Factor VIII Complex - Allain, J P; Croissant, M P; Lerolle, D; Houbouyan, L; Zuzel, M; Frommel, D (Thrombosis and Haemostasis, 1982)
Two non-haemophilic elderly patients who had developed autoantibodies to factor VIII were studied over a period of 9 months to 5 years. Sequential measurements of antibody to factor VIII (anti-VIII: C), factor VIII coagulant activity (VIII: C), factor VIII coagulant antigen (VIII: CAg), factor VIII-related antigen (VIIIR: Ag), and factor VIII ristocetin cofactor (VIII: WF) were performed. Before treatment, low VIII: C, norlnal or increased VIII: CAg and high VIIIR: Ag levels were found and were indicative of the presence of circulating immune complexes. Immunosuppressive therapy induced progressive correction of VIII: C and VIIIR: Ag values. High levels of VIII: CAg subsided in the patient who relapsed. It is suggested that antibodies to factor VIII bind and remove VIII: C from the circulation thereby inducing an increased synthesis of VIII: CAg which may be associated with an augmented release or production of VIIIR: Ag.
Keywords: Autoantibody; Acquired haemophilia; Factor VIII complex; IRMA; Immunosuppressive therapy